Fabrication of polyimide hollow fiber membrane with well‐defined adsorption channels and binding sites for organics separation. Issue 7 (16th August 2017) - Lin, Ligang; Sun, Hui; Cheng, Qi; Huang, Kai; He, Zhifu; Zheng, Tiantian; Zhang, Yuzhong
Abstract : Significant attention has been focused in developing polymeric membranes with special separation function. Disclosed herein is the design of a solvent resistant hollow fiber membrane with multi architectures including self‐supported passageway, three‐dimensional adsorption channels, and binding sites for organics sulfur. A new strategy has been proposed for high‐performance polyimide hollow fiber membranes by tuning the imidization behavior. The evolution of structure and performance with the proposed imidization routes has been investigated based on detailed analysis of FT‐IR, TGA, and mechanical properties. The results show that the functional zeolites are incorporated into three‐dimensional polyimide matrix. The well‐defined transport channels at micrometer scale in membrane provide high‐efficiency working space. The effective binding behavior of designed hollow fiber membrane chromatography for organic sulfur compounds has been confirmed by the comparative analysis on dynamic breakthrough curves. The related discussions have some general suggestions in promoting the new application of membrane chromatography for the quick separation and purification of sulfur, and present a potential alternative for the production of sulfur‐free hydrogen source for fuel cell applications. POLYM. ENG. SCI., 58:1024–1032, 2018. © 2017 Society of Plastics Engineers